Unformatted text preview: k = 0 and see that the term goes to v . To evaluate the limit of the ﬁrst term, we use L’Hˆ opital’s rule: lim k → mg (1 + ekt/m ) k = mg lim k →t m ekt/m 1 =gt Putting it all together, we have that lim k → v = vgt If we instead considered m → 0, note that ekt/m → 0 for t > 0, so we immediately see lim m → v = 0...
View
Full
Document
This note was uploaded on 07/17/2008 for the course MATH 415 taught by Professor Costin during the Fall '07 term at Ohio State.
 Fall '07
 COSTIN
 Differential Equations, Equations

Click to edit the document details